State Transitions During Discrimination Learning in the Gerbil Auditory Cortex Analyzed by Network Causality Metrics - Kozma, Robert; Hu, Sanqing; Sokolov, Yury; Wanger, Tim; Schulz, Andreas L.; Woldeit, Marie L.; Gonçalves, Ana I.; Ruszinkó, Miklós; Ohl, Frank W. (Frontiers in Systems Neuroscience, 2021)
{\it \tiny Dedication: This work is dedicated to the memory of our dear colleague and friend Sanqing Hu, who relentlessly pursued research at the forefront of science, leading to the discoveries reported in this work. Without him these results would not exist.} This work studies the evolution of cortical networks during the transition from escape strategy to avoidance strategy in auditory discrimination learning in Mongolian gerbils trained by the well-established two-way active avoidance learning paradigm. The animals were implanted with electrode arrays centered on the surface of the primary auditory cortex and electrocorticogram (ECoG) recordings were made during performance of an auditory Go/NoGo discrimination task. Our experiments confirm previous results on a sudden behavioral change from the initial na\"ive state to an avoidance strategy as learning progresses. We employed two causality metrics using Granger Causality (GC) and New Causality (NC) to quantify changes in the causality flow between ECoG channels as the animals switched to avoidance strategy. We found that the number of channel pairs with inverse causal interaction significantly increased after the animal acquired successful discrimination, which indicates structural changes in the cortical networks as a result of learning. A suitable graph-theoretical model is developed to interpret the findings in terms of cortical networks evolving during cognitive state transitions. Structural changes lead to changes in the dynamics of neural populations, which are described as phase transitions in the network graph model with small-world connections. Overall, our findings underscore the importance of functional reorganization in sensory cortical areas as a possible neural contributor to behavioral changes.